Flow analyses and efficiency-enhancement approach for 2-D symmetrical aerohydrofoils at high Reynolds numbers - Celik, Fahri; Yilmazturk, Ogulcan; Karakurt, Asim Sinan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Symmetrical airfoils/hydrofoils are extensively employed in ship rudders, propeller blades, hydrofoil vessels, tidal turbines, turbomachinery components, and aircraft due to their balanced lift and drag characteristics over a wide range of flow conditions. This study presents the results of numerical flow simulations performed on four two-dimensional (2D) symmetrical foils of various thicknesses at Reynolds numbers (Re) of 2 & times; 106, 4 & times; 106, and 6 & times; 106. The flow is modeled as steady and turbulent using the Reynolds-Averaged Navier-Stokes (RANS) equations, which are solved by the finite volume method on an unstructured mesh. After successfully validating each Re, the study evaluated the impacts of thickness, Re, and angle of attack on aero-hydrodynamic performance and flow characteristics. Particular emphasis was placed on drag, examining the influence of flow features on drag components alongside the underlying physical mechanisms. The study identified and comparatively analyzed remarkable points regarding total drag and its component curves. We additionally investigated the potential of lift-enhancing devices to improve performance for the thinnest and thickest profiles (NACA 0009 and NACA 0021). The results indicate that a leading-edge Krueger flap on NACA 0009 can increase lift and reduce drag, achieving up to a 23% improvement in efficiency. For NACA 0021, Gurney and Fowler flaps provided lift augmentation and up to 12% greater efficiency. Unlike previous studies, this work focuses on explaining unconventional drag behaviors, such as drag reduction with increasing thickness or angle of attack (AOA) and unexpected drag rises, and further evaluates leading- and trailing-edge flap applications primarily to improve aerohydrodynamic efficiency through drag control rather than lift enhancement. While these findings offer valuable insights into the roles of profile geometry, Re, and flow control devices for optimizing performance, they should be treated as initial design benchmarks, as 3D effects must be considered for final engineering applications.
Keywords: Airfoil; Hydrofoil; Aerodynamic performance; Flow characteristics; Efficiency-enhancing device; Numerical analysis; AERODYNAMIC CHARACTERISTICS; THICKNESS; FLAP; Engineering; Oceanography